2021
DOI: 10.3389/fpsyg.2021.648087
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Compassion and Mindfulness-Based Cognitive Mobile Intervention (Serene) for Depression, Anxiety, and Stress: Promoting Adaptive Emotional Regulation and Wisdom

Abstract: Introduction: Many individuals and families are currently experiencing a high level of COVID-19-related stress and are struggling to find helpful coping mechanisms. Mindfulness-based interventions are becoming an increasingly popular treatment for individuals experiencing depression and chronic levels of stress. The app (Serene) draws from scholarly evidence on the efficacy of mindfulness meditations and builds on the pre-existing apps by incorporating techniques that are used in some therapies such as cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 72 publications
2
27
1
1
Order By: Relevance
“…Psychosocial interventions have been considered the most effective ways to reduce distress, alleviate psychological symptoms and promote psychological resilience during the ongoing pandemic ( Al-Refae et al, 2021 ; Dawel et al, 2020 ; Galea et al, 2020 ). However, such interventions rarely included actions to reduce PSW.…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial interventions have been considered the most effective ways to reduce distress, alleviate psychological symptoms and promote psychological resilience during the ongoing pandemic ( Al-Refae et al, 2021 ; Dawel et al, 2020 ; Galea et al, 2020 ). However, such interventions rarely included actions to reduce PSW.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve studies of psychological interventions on people during the SARS-CoV-2 pandemic were identified for inclusion [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. All studies were published in 2020 and 2021 and published in indexed journals.…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes ranged from 9 participants to 1500 participants. Seven studies included patients, of which three studies included people with a mean age ranging from 40.8 to 48.3 years [ 19 , 24 , 25 ], two studies included people with a mean age ranging from 34.6 to 36.8 years [ 22 , 26 ], and two studies included younger people with a mean age ranging from 26.1 to 28.5 years [ 23 , 28 ]. Another study included health care workers without personal identifying information being collected [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we have shown that scores on the original SD-WISE are reliable, valid, and have positive correlations with measures of good mental health and well-being as well as negative correlations with measures of poor mental health (Jeste et al, 2021). The scale is increasingly being used in large national and international studies (Jeste et al, 2020a(Jeste et al, , 2020bNguyen et al, 2020), biological research (Grennan et al, 2021;Nguyen et al, 2021;Thomas et al, 2019b), and clinical trials (Treichler et al, 2020), including a recent study that demonstrated positive change in specific components of the SD-WISE following a mindfulness intervention (Al-Refae et al, 2021).…”
Section: Introductionmentioning
confidence: 99%